(x5-5)⋅(x5+5)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x5-5=0

x5+5=0

Set the first factor equal to 0.

x5-5=0

Add 5 to both sides of the equation.

x5=5

Multiply both sides of the equation by 5.

5⋅x5=5⋅5

Simplify both sides of the equation.

Cancel the common factor of 5.

Cancel the common factor.

5⋅x5=5⋅5

Rewrite the expression.

x=5⋅5

x=5⋅5

Multiply 5 by 5.

x=25

x=25

x=25

Set the next factor equal to 0.

x5+5=0

Subtract 5 from both sides of the equation.

x5=-5

Multiply both sides of the equation by 5.

5⋅x5=5⋅-5

Simplify both sides of the equation.

Cancel the common factor of 5.

Cancel the common factor.

5⋅x5=5⋅-5

Rewrite the expression.

x=5⋅-5

x=5⋅-5

Multiply 5 by -5.

x=-25

x=-25

x=-25

The final solution is all the values that make (x5-5)⋅(x5+5)=0 true.

x=25,-25

Solve for x (x/5-5)*(x/5+5)=0